Kompetensi Manajerial Kepala Sekolah dalam Perencanaan Peningkatan Mutu Pendidikan di SMK : Kajian Literatur - Rina Wati; Ernawati Ernawati; Jonni Mardizal (Journal on Education, 2024)
This study aims to analyze the role of principals' managerial competence in planning to improve the quality of education in Vocational High Schools (SMK). The method used is the Systematic Literature Review (SLR) by reviewing articles published between 2019 and 2024. The results of the review show that principals with good managerial competence are able to formulate relevant visions, missions, and strategies to improve the quality of education in SMK. These competencies also play a role in resource management, curriculum development, and evaluation of educational programs. However, challenges such as lack of managerial training and limited resources are still obstacles in the implementation of quality planning in several schools. This article provides recommendations for strengthening principals' managerial training programs to support the sustainability of improving the quality of education in SMK.